Maternal and fetal outcome in cardiac disease in pregnancy: a retrospective study at tertiary care center - Behera, Ritanjali; Moharana, Jayashree J. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Cardiac disease in pregnancy is a high-risk pregnancy and major problem worldwide particularly developing countries. In present scenario the incidence of pregnancy with congenital heart disease is high in developed countries and they are landing with favourable outcome due to advance surgical correction of the defects. In developing countries, the incidence of RHD is still high. Therefore, in this study we aim to analyse the incidence of cardiac disease in pregnancy in our hospital and to assess the obstetric outcome. Methods: A retrospective study carried out in 22 number of patients with cardiac disease at tertiary care center during the period of 2 years. Results: In present study the incidence of cardiac disease in pregnancy was observed to be 0.15%.Among them the prevalence of RHD was high (68.1%).Out of which the most common valvular lesion was mitral stenosis (46.6%) followed by mitral stenosis with mitral regurgitation (26.6%).50% of the patients were in NYHA class 2.Majority delivered vaginally with instrumental application in second stage (95.4%).Obstetric complications observed in form of anaemia, preeclampsia, abruption placentae and preterm labour and one maternal mortality. Perinatal morbidities observed in form of prematurity, SGA, birth asphyxia, MSAF, NICU admission. Conclusions: cardiac disease has major impact on pregnancy and its outcome. It is a team effort by obstetrician, cardiologist, neonatologist to achieve successful pregnancy. Regular antenatal checkup and strict vigilance during the risk period when patient may develop complications as a result of haemodynamic changes can avoid the complications.